SEMANTIC ANALYSIS IN TRANSLATING CULTURAL ELEMENTS IN THE NOVEL "PACHINKO" BY MIN JIN LEE - Pertiwi, Gema; Sari Dewi, Ika (La Ogi : English Language Journal, 2024)
Semantic analysis is a study that explores meaning in language, whether in the form of words, phrases, sentences, or entire texts. This academic work is presented to analyze the translation.. This research aims to analyze the translation of cultural elements in the novel "Pachinko" by Min Jin Lee through a qualitative approach. The main source of data is the novel "Pachinko" itself, which contains representations of complex cultural elements. The data analysis technique used is Word Analysis, that is, Semantic Analysis can find words and phrases related to character changes, such as "identity," "citizenship," "discrimination," and "crisis," and then Idea Analysis, that is, Semantic Analysis can find ideas and concepts related to character changes, such as "generation," "immigration," and "downturn". Thus, this analysis can help understand how character changes are related to how the characters in the novel interact with their environment and how they face challenges. The cultural elements in this novel are analyzed using a Referential approach and it is found 45%, an Ideasional approach 25%. Then the Behavioral approach 13%, and also a Pragmatic approach 17%.